KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN PADA KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PURBALINGGA - Silfianita, Melly; Purboyo, Taufik (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2024)
Population administration services are a series of activities to organize and control population documents and data that are continuous. With quality public services, it will increase the satisfaction of service users. However, in reality, the services carried out by the government show almost the same symptoms in various government service sectors which lead to public dissatisfaction as consumers, one of which occurs in Purbalingga Regency, especially at Dinpendukcapil. This study aims to analyze and describe the quality of population administration services at the Population and Civil Registration Office of Purbalingga Regency. The method used in this research is descriptive qualitative. The data used are primary and secondary data obtained through observation, interviews and documentation. The results showed that the quality of population administration services at Dinpendukcapil Purbalingga Regency was not optimal. Based on the results of the study, it can be recommended that the quality of population administration services at the Purbalingga Regency Dinpendukcapil Office needs to improve facilities and infrastructure and further improve how population administration services are provided.